EXPLORING EFL STUDENTS’ EXPERIENCE AND CHALLENGES IN DIGITAL STORYTELLING-BASED LISTENING ACTIVITIES AT VOCATIONAL HIGH SCHOOL - Aulia, Tazkia; Indah Purnama Dewi; Totoh Tauhidin Abas (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study explored students’ experiences and challenges in learning listening through digital storytelling at a private vocational high school in Subang. Many EFL learners face listening comprehension difficulties, especially in understanding unfamiliar vocabulary, following spoken input, and maintaining concentration. Therefore, this study aimed to gain a deeper understanding of how digital storytelling shapes EFL learners’ listening learning process. A qualitative case study design was employed involving six tenth-grade students selected based on their participation during digital storytelling lessons. Data were collected through classroom observations, semi-structured interviews, and documentation. The data were analyzed using the interactive model of Miles, Huberman, and Saldana (2013), which consists of data condensation, data display, and conclusion drawing. The findings revealed that students generally had positive experiences with digital storytelling. They showed enjoyment and interest, used visual elements to support story comprehension, reported positive changes in pronunciation awareness and vocabulary acquisition, and engaged in collaborative discussion. However, students also encountered challenges, including unfamiliar vocabulary, difficulty following the pace of narration, and fluctuating concentration. To cope with these difficulties, they relied on visual cues, subtitles, teacher explanations, and peer discussion. The study concludes that digital storytelling provides meaningful listening experiences and supports students’ engagement when accompanied by vocabulary preparation and listening guidance.